Design and Implementation of Discrete Multitone Modulator for Digital Subscriber Line Using FPGA - Hadi T. Ziboon; Ikhlas M. Farhan (Engineering and Technology Journal, 2014)
This paper presents a design, simulation and implementation of the Discrete Multitone (DMT) modulator for digital subscriber line (DSL) for both complex and real transmission based on Software Defined Radio (SDR) using FPGA. DMT divides the available bandwidth into parallel sub-channels. There are two techniques to transmit data by DMT. Complex transmission and real transmission .Real transmission is preferred for DSL, since it needs single wire but uses twice number of IFFT. The Simulink HDL Coder has been used for converting the MATLAB-Simulink and M-files models to VHDL language. The verification of the generated VHDL code has been done using Altera- ModelSim, while the synthesis reports and board programming files have been obtained using the Quartus II. The FPGA is used as a platform for SDR. The implementation by using Simulink HDL coder shows the feasibility and flexibility in solving the problems of implementation of the main units of DMT for both complex and real transmission. The main units of DMT are serial to parallel converter,MQAM,IFFT,Parallel to serial and cyclic prefix. The experimental results show that there is coincidence between generated real and complex signal and simulated real and complex signal by generated MATLAB (Simulink and M-file) and Simulink HDL Coder.